An examination of the association between 5-HTTLPR, combat exposure, and PTSD diagnosis among U.S. veterans. - Yutao Liu; Melanie E Garrett; Michelle F Dennis; Kimberly T Green; VA Mid-Atlantic MIRECC Registry Workgroup; Allison E Ashley-Koch; Michael A Hauser; Jean C Beckham; Nathan A Kimbrel (PLoS ONE, 2015)
To examine the association between the 5-HTTLPR polymorphism of the serotonin transporter (SLC6A4) gene, combat exposure, and posttraumatic stress disorder (PTSD) diagnosis and among two samples of combat-exposed veterans.The first sample included 550 non-Hispanic Black (NHB) combat-exposed veterans. The second sample included 555 non-Hispanic White (NHW) combat-exposed veterans. Participants were genotyped for the 5-HTTLPR/rs25531 variants of the SLC6A4 gene. A structured clinical interview was used to diagnose PTSD. Combat and civilian trauma exposure were assessed with validated self-report instruments. Logistic regression was used to test for main effects of 5-HTTLPR on PTSD diagnosis as well as gene x environment (GxE) interactions after adjusting for sex, ancestry proportion scores, civilian trauma exposure, and combat exposure.Within the NHB sample, a significant additive effect was observed for 5-HTTLPR (OR = 1.502, p = .0025), such that the odds of having a current diagnosis of PTSD increased by 1.502 for each additional S' allele. No evidence for an association between 5-HTTLPR and PTSD was observed in the NHW sample. In addition, no evidence for combat x 5-HTTLPR effects were observed in either sample.The present study suggests that there may be an association between 5-HTTLPR genotype and PTSD diagnosis among NHB veterans; however, no evidence for the hypothesized 5-HTTLPR x combat interaction was found.